2010
DOI: 10.1155/2010/464087
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of the Extracts Obtained from Rosmarinus officinalis, Origanum majorana, and Trigonella foenum-graecum on Highly Drug-Resistant Gram Negative Bacilli

Abstract: Our aim was to determine the antimicrobial activity of three selected plants (Rosmarinus officinalis, Origanum majorana, and Trigonella foenum-graecum) against Extended Spectrum Beta Lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae-and to identify the specific plant fraction responsible for the antimicrobial activity. The plants were extracted with ethanol to yield the crude extract which was further subfractionated by different solvents to obtain the petroleum ether, the dichloromethane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The antimicrobial potential of plant species has been explored mostly via studies of their essential oils (EOs) [12,13,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Due to the toxic effect exhibited by EOs, it is of utmost importance to explore other plant-derived therapeutic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial potential of plant species has been explored mostly via studies of their essential oils (EOs) [12,13,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Due to the toxic effect exhibited by EOs, it is of utmost importance to explore other plant-derived therapeutic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Origanum majorana was highly inhibitory to the growth of Staphylococcus aureus, recording the lowest MIC in this study with the dichloromethane, ethyl acetate and aqueous extracts which were all 0.625μg/μl (Table 3). Similarly, Abdel-Massih et al 38 showed that the ethyl acetate fraction of Origanum majorana had the best antimicrobial effect on E. coli and K. pneumoniae exhibiting the lowest MIC 90 (1.28 μg/μl). Leeja et al 28 also studied the antimicrobial activity of Origanum majorana against Staphylococcus aureus using the disc diffusion method.…”
Section: Antimicrobial Activity Of Rheum Rhaponticummentioning
confidence: 92%
“…Several additional studies that stretch beyond the scope of single-center studies are needed as well in order to shed light on the prevalence of resistance across the country. Nevertheless, few novel studies targeting endogenous plants are being conducted in Lebanon in an attempt to discover new molecules that exert antibiotic activity [54,55]. Whether these attempts would be successful and helpful in the ongoing effort to combat resistant strains remains to be unveiled.…”
Section: Antimicrobial Consumption and Conclusionmentioning
confidence: 99%